Satisfaction of outpatients on service quality: a case study at two specialist clinics - Choong-Yeun Liong; Nur Jumaadzan Zaleha Mamat; Tze-Yun Leong (Penerbit ukm, 2009)

(untitled)
Since the last few decades, there has been a growing concern on the issues of health care, particularly on the service quality provided by hospitals. Generally all hospitals aim at providing the best quality of services to their patients but the service quality may vary between hospitals. A case study was carried out for measuring outpatients’ satisfaction on the service quality at two specialist clinics using the quality dimensions as proposed by the Joint Commission on Accreditation of Healthcare Organizations. By using gap analysis and quality value, i.e. Q method, eight dimensions of quality service that were studied include appropriateness, efficiency, respect and caring, safety, continuity, effectiveness, timeliness, and availability. The study showed that the service quality provided by these two specialist clinics were unable to meet the expectations of the outpatients